Packaging Cost Control Among Traditional Tamarind Traders in Pasar Terong Makassar - Rita Yani; Wa Ode Rayyani (Jurnal Studi Multidisiplin Ilmu, 2025)
Purpose: This study analyzes packaging cost control practices through an informal control system applied by traditional tamarind traders in Pasar Terong Makassar, and evaluates these practices from a sharia perspective concerning the prohibition of tabzir and israf. Methodology: The study uses a qualitative approach with a case study method. Data were collected through in-depth interviews, direct observation, and documentation. Informants were selected through purposive sampling, comprising tamarind traders, buyers, and market officials at Pasar Terong Makassar.Results: The findings show that traditional tamarind traders apply informal packaging cost control through memory-based accounting, manual physical control based on hand-weighed portions, and direct owner oversight. This practice aligns with sharia principles of avoiding tabzir and israf in pursuit of business blessing (barakah). Conclusions: Packaging cost control among traditional tamarind traders in Pasar Terong Makassar is carried out through an effective informal system despite the absence of formal bookkeeping. Religious moral values function as a natural internal control instrument that supports cost efficiency and business sustainability. Limitations: This study is confined to tamarind traders at Pasar Terong Makassar, so its findings cannot be directly generalized to different traditional trading contexts.Contributions: This study contributes to the development of informal management accounting literature in the traditional MSME sector and enriches the study of sharia value integration in the operational cost control of traditional market traders.